Mutant Isocitrate Dehydrogenase Inhibitors as Targeted Cancer Therapeutics - Golub, Danielle; Iyengar, Nishanth; Dogra, Siddhant; Wong, Taylor; Bready, Devin; Tang, Karen; Modrek, Aram S.; Placantonakis, Dimitris G. (Frontiers in Oncology, 2019)
The identification of heterozygous neomorphic isocitrate dehydrogenase (IDH) mutations across multiple cancer types including both solid and hematologic malignancies has revolutionized both our understanding of oncogenesis in these malignancies and the potential for targeted therapeutics using small molecule inhibitors. This neomorphic mutation in IDH generates an oncometabolite product, 2-hydroxyglutarate (2HG), which has been linked to the disruption of metabolic and epigenetic mechanisms responsible for cellular differentiation and is likely an early and critical contributor to oncogenesis. In the past two years, two mutant IDH (mutIDH) inhibitors, Enasidenib (AG-221) and Ivosidenib (AG-120), have been FDA-approved for IDH-mutant relapsed or refractory acute myeloid leukemia (AML) based on phase 1 safety and efficacy data and continue to be studied in trials in hematologic malignancies, as well as in glioma, cholangiocarcinoma, and chondrosarcoma. In this review, we will summarize the molecular pathways and oncogenic consequences associated with mutIDH with a particular emphasis on glioma and AML, and systematically review the development and preclinical testing of mutIDH inhibitors. Existing clinical data in both hematologic and solid tumors will likewise be reviewed followed by a discussion on the potential limitations of mutIDH inhibitor monotherapy and potential routes for treatment optimization using combination therapy.